Rare case report: Liver metastasis from cervical adenocarcinoma presenting with cystic mass and obstructive jaundice - Li, Jin; Wei, Xin; Luo, Le (Frontiers in Oncology, 2025)
Liver metastases can originate from primary tumors in various organs; however, metastasis from cervical cancer to the liver is rare. Cervical cancer patients with distant metastases have a poor prognosis and reduced survival rates. This report describes a case of a cystic liver mass with obstructive jaundice, observed four years after resection of cervical adenocarcinoma. The lesion lacked typical imaging characteristics of hepatic metastases and was initially suspected to be a biliary neoplasm. A contrast-enhanced, ultrasound-guided needle biopsy was performed to confirm the diagnosis. Histopathological analysis confirmed adenocarcinoma of the liver, and immunohistochemical staining suggested a uterine or adnexal origin. Considering the patient’s surgical history, the final diagnosis was liver metastasis originating from cervical adenocarcinoma. This report reviews relevant literature to discuss the clinical features, diagnostic challenges, and therapeutic strategies for liver metastasis of cervical cancer.